A conceptual model of virtual product development process - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (2009)
In today’s dynamic marketplace, companies are under strong pressure to introduce new products for long-term survival with their competitors. Besides, every company cannot cope up progressively or immediately with the market requirements due to knowledge dynamics being experienced in competitive milieu. Increased competition and reduced product life cycles put force upon companies to develop new products faster. In response to this pressing need there should be some new approach compatible in flexible circumstances. This paper presents a solution based on the Stage-Gate system, which is closely linked with virtual team approach. Virtual teams can provide a platform to advance the knowledge-base in a company and thus to reduce time-to-market. This article introduces conceptual product development architecture under a virtual-team umbrella. The paper describes all the major aspects of new product development (NPD), NPD process and its relationship with virtual team, Stage-Gate system and finally presents a modified Stage-Gate system. It also provides the guidelines for the successful implementation of virtual team in new products development.